PEMBERIAN Soybean oligosaccharides DARI EKSTRAK BUNGKIL DAN KULIT KEDELAI TERHADAP pH USUS, POPULASI E. coli, dan PBBH PADA BROILER - Melinda E Krismaputri; N Suthama; Y. B. Pramono (MEDIAGRO, 2016)
The study aims to examine the influence of prebiotic Soybean oligosaccharides (SOS) from soybean meal extract (SME) and soybean hull extract (SHE) on the potential of hydrogen (pH) intestine, Escherichia coli (E. coli) population, and daily body weight gain (DBWG) in broiler chickens. The research material was 160 broiler chickens Lohman strain unsex maintained for 6 weeks. The study used a completely randomized design with 5 treatments and 4 replications, each replication uses 8 broiler chickens. Feeding treatments were: T0 (basal diet/ BD), T1 (BD + 0,15% SME), T2 (RB + 0,3% SME), T3 (RB + 0,15% SHE), T4 (RB + 0,3% SHE). The data were analyzed using ANOVA followed by Duncan multiple range test. The results showed that administration of prebiotic SOS from SME and SHE at all levels not significantly (p>0,05) against pH intestine, but significant (p<0,05) on E. coli population and DBWG in broiler chickens.   Keywords: DBWG, E. coli, pH, soybean meal and hull, soybean oligosaccharides